The Influence Of Brand Image, Brand Trust, And Purchase Intention As Mediating Variables On Purchasing Decisions At Mcdonald’s In Semarang City - Khasanah, Nur Khikmah; Setiawati, Ira; P, Ratih Hesty Utami (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of Brand Image, Brand Trust, and Purchase Intention as mediating variables on purchasing decisions at McDonald’s in Semarang City. This study is structured using quantitative research, utilizing a questionnaire as the research instrument. The sample in this study consists of 400 respondents. The sample was taken using a non-probability sampling method because the total population size is unknown. The research data were analyzed using the statistical method of Structural Equation Modeling (SEM) with the Smart PLS 3 application. This study has data that has met the validity and reliability tests, indicating that the data results meet the requirements for the model to proceed to hypothesis testing. The results of this study indicate that: (1) Brand Image affects purchase intention, (2) Brand Trust affects purchase intention, (3) Brand Image affects purchasing decisions, (4) Brand Trust affects purchasing decisions, (5) Purchase intention affects purchasing decisions, (6) Brand Image affects purchasing decisions mediated by purchase intention, and (7) Brand Trust affects purchasing decisions mediated by purchase intention.